THE GROWTH HORMONE RECEPTOR (GHR) POLYMORPHISM IN GROWTH-RETARDED CHILDREN WITH CUSHING DISEASE: LACK OF ASSOCIATION WITH GROWTH AND MEASURES OF THE SOMATOTROPIC AXIS - Drori-Herishanu, Limor (2009)
OBJECTIVE: Pediatric Cushing disease (CD) often presents with short stature but we have observed significant inter-individual variability in the growth delay caused by endogenous hypercortisolism. Glucocorticoids cause growth retardation by affecting the growth hormone (GH) – insulin-like growth factor-1 (IGF 1) somatotropic axis, but also other, GH-independent sites. Recently, the GH receptor (GHR) gene was found to have a common polymorphism (P) that leads to a deletion (d3) or retention of exon 3. In this study, we tested the hypothesis that the GH receptor polymorphism (GHR-P) maybe one of the significant variants that determine the degree of growth delay among patients with CD. DESIGN AND METHODS: GHR genotyping was performed on 56 children with newly diagnosed CD (24 females, 32 males, mean age of 12.9±3.3 years) who were followed at our institution between the years 1997–2007. Correlation analysis included genotype, measures of growth and the somatotropic axis, and anthropometrics. RESULTS: Within the group, 31 (12 girls, 19 boys) expressed the full length GHR allele, 10 (4 girls, 6 boys) were d3-GHR homozygotes and 15 (7 girls, 8 boys) were d3-GHR heterozygotes. No significant differences were found between the GHR genotypes and patient’s height and or growth velocity, or any other measures that we evaluated. CONCLUSIONS: The presence of a well-studied and common GHR polymorphism does not appear to be responsible for the variability of growth delay observed in patients with Cushing disease.